Unsur-unsur Filsafat Sejarah dalam Pemikiran R.NG. Ronggowarsito - Dian Widiyanarko (Jurnal Filsafat "WISDOM", 2004)
Ronggowarsito is one Indonesian's philosophers who has inheritated so many principles fo philosophy. One of them is the philosophy of history, which he has written in his several works such as Paramayoga, Pustakaraja, Purwa, Kalatidha, Sabda Jati, etc this paper will explore the elements of philosophy of history in Ronggowarsito's thought and compare it with modern thought about philosophy of history, especially western philosophy. From this exploration and comparation we will know Ronggowarsito's thought about philosophy of history.